Experience capitalization: Learning as a facilitator? Definitely! - Kompaoré, Yennenga (Technical Centre for Agricultural and Rural Cooperation, 2019)
In January 2017 I was contacted by CTA and asked to be part of a group of facilitators working together in the project called “Experience Capitalization for Greater Impact in Rural Development”. I had some experience in this field, but this seemed like a different initiative. We worked together for a few months, and we have seen quite a bit, and we have also learned a lot. And I am sure that we will see much more in the future.